Why Does Hazardous and Toxic Waste Continue to Pose a Threat to Mulya Asri Village? - Habibah, Corrist Fatihal Salwa; Mahmudah, Siti; Frenki, Frenki (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The management of household hazardous (B3) waste in rural areas continues to face significant challenges related to regulatory frameworks, public awareness, and the integration of Islamic values. This study aims to analyze the role of the Environmental Service in managing hazardous waste and to offer strategic recommendations grounded in existing regulations and the principles of Fiqh Siyasah Tanfidziyah to enhance B3 waste management in Mulya Asri Village, West Tulang Bawang Regency. A qualitative descriptive method was employed, utilizing interviews, observations, and document analysis. The findings reveal that the implementation of regional policies remains suboptimal, hindered by inadequate infrastructure, limited public education, and insufficient integration of Islamic principles concerning environmental stewardship. The study concludes that improving B3 waste management requires the integration of regional policies with a religiously informed welfare-based approach. It recommends strengthening regulatory frameworks, promoting Islamic-based environmental education, and fostering cross-sector collaboration at the village level.